Bioelectrochemical Systems: Microbial Electrolysis Cell for Hydrogen Production - Castro, Alex S. [UNESP] (2024)
Systems that utilize the ability of microorganisms to receive or produce electrical current are known as bioelectrochemical systems (BES). In this review, the microbial electrolysis cell (MEC) will be addressed as an alternative for the sustainable and renewable production of hydrogen (H2). With varied applications, MEC can generate H2 from low-cost organic substrates, using residues. In a MEC, microorganisms are used as biocatalysts at the anode to oxidize, usually residual organic matter resulting in CO2, protons, and electrons. Electrons go through an external circuit, while protons traverse a semipermeable membrane. Both are transported to the cathode where electrons reduce the protons, resulting in H2. Technological advances in recent decades have led to an improvement in H2 production yields in MEC. This article presents a didactic view of MEC, introducing definitions, theoretical concepts, and critical factors, such as the development of new cathodes, the form of capture and detection of hydrogen, and experimental conditions of microorganisms, which affect the performance of a MEC.